Autistic People's Access to Bilingualism and Additional Language Learning: Identifying the Barriers and Facilitators for Equal Opportunities - Davis, Rachael; Fletcher-Watson, Sue; Digard, Bérengère G. (Frontiers in Psychology, 2021)
Bilingualism is a valuable tool that enriches and facilitates cultural, social and lived experiences for autistic and non-autistic people alike. Research consistently finds no negative effects of bilingualism and highlights the potential for positive effects across cognitive and socio-cultural domains for autistic and non-autistic children. Yet parents of autistic children remain concerned that bilingualism will cause delays in both cognitive and language development and are still frequently advised by practitioners to raise their child monolingually. Evidently, findings from research are not reflected in practice or subsequent advice, and it is essential to identify ways to ensure equal access to additional language learning. We briefly summarise the existing literature on bilingualism and autism, considering perspectives from the bilingual autistic community, and experimental research. We identify the most pertinent barriers to participation for autistic bilingual children in terms of familial, clinical and educational perspectives. We propose novel solutions to promote additional language learning, and suggest changes to practice that will contribute to an evidence base for families and practitioners. This commentary makes innovative recommendations at both the individual and societal level to ensure that autistic bilingual people have equal rights and opportunities to language learning and are optimally supported in accessing them.